Case Report: Pitfalls in bone marrow evaluation: importance of adequate bone marrow sampling - Ghezavati, Alireza; Vali Betts, Elham; Datta Mitra, Ananya (Frontiers in Oncology, 2025)
Bone marrow evaluation is a powerful diagnostic tool, but it comes with several potential pitfalls. These include issues related to sampling errors, technical challenges during processing, and misinterpretation of the findings due to similarities between various diseases. Awareness of these pitfalls, adopting a systematic approach of reviewing the bone marrow samples, and carefully integrating clinical information are critical to ensuring accurate diagnosis. Using ancillary techniques, such as immunohistochemistry (IHC), can further aid in distinguishing between benign reactive changes and malignant processes, reducing the likelihood of diagnostic errors. Bone marrow sampling is inherently challenging, and improper or inadequate sampling is one of the most common reasons for diagnostic failure. Moreover, the process of collecting and preparing the bone marrow samples, leading to aspicular aspirate smears with hemodilution, or tissue preparation techniques like decalcification procedures in the core biopsy, leading to IHC stain failures, may add to the diagnostic challenges in bone marrow evaluation. Lastly, inherent properties of some diseases or the presentation of abnormal findings with focal involvement or obscuring of morphology in an inflammatory background can pose a potential diagnostic challenge. In this article, we present three diagnostically challenging cases that highlight potential pitfalls in bone marrow evaluation, along with a brief review of the literature, and describe strategies to avoid diagnostic errors based on our institutional experience.